Environmental litigation in Nigeria: the role of the judiciary (2019)
Environmental laws are put in place to mitigate the threatening environmental problems resulting from human activities. To checkmate these human activities, courts are established by governments with jurisdictions to entertain environmental litigations to protect and redress environmental wrongs in Nigeria. The aim of this paper is to appraise environmental litigation under the Nigerian jurisprudence and the role of judiciary in resolving such matter. To achieve this objective, the questions which the paper seeks to interrogate among others include: What role has judiciary played in promoting and protecting the right to a healthy environment in Nigeria? What are the jurisdictional obstacles militating against the use of litigation to protect and redress environmental wrongs in Nigeria? In answering these questions, this paper discusses the nature of Nigerian environmental litigations and courts confer with jurisdiction to entertain environmental litigation. The paper examines various impediments to environmental litigations in Nigeria. The paper argues for the encouragement of private and public interest litigation and creation of procedure for enhancing public participation in Nigerian environmental protection. The paper concludes with recommendation for the establishment of environmental court.